Regional Specialization via Differences in Transport Costs: An Economic Geography Approach - Hajime Takatsuka; Dao-Zhi Zeng (European Regional Science Association (ERSA), 2004)
The regional specialization via differences in transport costs are observed in Japanese manufacturing industries. Concretely, industries with high transport costs for their products, such as iron and steel, petroleum and coal products, remained close to the core region while industries with low transport costs, such as electrical machinery, precision instruments, have relocated to the periphery region. The purpose of this paper is to give a theoretical foundation for this fact by use of a new economic geography model with multiple industries. The urban costs and congestion are explicitly included in the model. We obtain the following results. First, if congestion does not exist, at most one industry disperses when transport and commuting costs are sufficiently small. Furthermore, regional specialization occurs in which industries having higher adjusted transport costs (which are defined as the ratios of transport costs to the number of varieties) than that of the dispersing industry agglomerate in one region. Second, in the case of strong congestion, plural industries might disperse even if transport and commuting costs are small, but as the degree of congestion decreases, the location will change to complete regional specialization. Keywords: regional specialization, economic geography, transport costs, urban costs, congestion.
Keywords: 330; regional specialization; economic geography; transport costs; urban costs; congestion